Reversible Electroporation and Post-Electroporation Resting of Thai Basil Leaves Prior to Convective and Vacuum Drying - Grant Thamkaew; Allan G. Rasmusson; Dmytro Orlov; Federico Gómez Galindo (Applied Sciences, 2022)
Pretreatment by reversible electroporation followed by resting (storage under saturated moisture at 21 ± 2 °C) was evaluated for modification of the properties of dried and rehydrated Thai basil leaves. The treated leaves were dried by convection at 40 °C or in a vacuum at room temperature. The results showed that vacuum drying provoked more cell damage and tissue collapse than convective air drying at a moisture ratio (MR) of 0.2 and 0.1. Under this level of MR, the pulsed electric field (PEF) and resting pretreatment exerts a protective effect of the tissue for both drying methods. However, under complete dehydration (water activity, aw = 0.05) damage seems to be similar for both drying methods despite the PEF pretreatment. Remarkably, reversible electroporation followed by resting resulted in higher trichome preservation. At MR of 0.05, the area of trichomes on the surface of convective-dried, PEF-rested and fresh samples were not statistically different at 2267 ± 89 µm2 and 2218 ± 65 µm2, respectively, showing that this pretreatment still exerts a protective effect on trichomes when complete dehydration is achieved.